PENGARUH COST OF DEBT, BEBAN PAJAK PENGHASILAN DAN KEBIJAKAN DIVIDEN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN CONSUMER NON CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Suci Ayu Rahmawati; Wiwit Irawati (Universitas Pendidikan Nasional, 2022)
This study aims to examine and analyze the effect of the cost of debt, income tax burden and dividend policy on earnings management in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2017-2021. This research uses quantitative and associative research types from secondary data sources. The population used in this study were 104 consumer non-cyclicals companies listed on the IDX. The research sample was selected using a purposive sampling technique and a sample of 20 companies was obtained. Data collection techniques are documentation studies and non-participant observations. The data analysis technique used is panel data regression analysis with the Eviews 9 test tool. The results show that the cost of debt, income tax expense and dividend policy simultaneously influence earnings management in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2017- 2021.